Wits Architecture Student Works 1922-1980. Thomsen, AM. Cine Valhalla, sections A.Long B Cross 1939. - Thomsen, AM (My University, 2014)
Wits Architecture Student Works 1922-1980. Thomsen, AM. Valhalla Cine A-Long. B-Cross. 1939; Groundfloor Plan 1939
Wits Architecture Student Works 1922-1980. Thomsen, AM. Valhalla Cine A-Long. B-Cross. 1939; Groundfloor Plan 1939. Black ink
Keywords: Wits Architecture Student Works 1922-1980. Thomsen, AM. Valhalla Cine A-Long. B-Cross. 1939; Groundfloor Plan 1939